Prognostic Value of the WHO1973 and WHO2004/2016 Classification Systems for Grade in Primary Ta/T1 Non-muscle-invasive Bladder Cancer: A Multicenter European Association of Urology Non-muscle-invasive Bladder Cancer Guidelines Panel Study - van Rhijn, Bas W G; Hentschel, Anouk E; Bründl, Johannes; Compérat, Eva M; Hernández, Virginia; Čapoun, Otakar; Bruins, H Maxim; Cohen, Daniel; Rouprêt, Morgan; Shariat, Shahrokh F; Mostafid, A Hugh; Zigeuner, Richard; et al. (European urology oncology, 2021)
BACKGROUND: In the current European Association of Urology (EAU) non-muscle-invasive bladder cancer (NMIBC) guideline, two classification systems for grade are advocated: WHO1973 and WHO2004/2016. OBJECTIVE: To compare the prognostic value of these WHO systems. DESIGN, SETTING, AND PARTICIPANTS: Individual patient data for 5145 primary Ta/T1 NMIBC patients from 17 centers were collected between 1990 and 2019. The median follow-up was 3.9 yr. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Univariate and multivariable analyses of WHO1973 and WHO2004/2016 stratified by center were performed for time to recurrence, progression (primary endpoint), cystectomy, and duration of survival, taking into account age, concomitant carcinoma in situ, gender, multiplicity, tumor size, initial treatment, and tumor stage. Harrell's concordance (C-index) was used for prognostic accuracy of classification systems. RESULTS AND LIMITATIONS: The median age was 68 yr; 3292 (64%) patients had Ta tumors. Neither classification system was prognostic for recurrence. For a four-tier combination of both WHO systems, progression at 5-yr follow-up was 1.4% in low-grade (LG)/G1, 3.8% in LG/G2, 7.7% in high grade (HG)/G2, and 18.8% in HG/G3 (log-rank, p < 0.001). In multivariable analyses with WHO1973 and WHO2004/2016 as independent variables, WHO1973 was a significant prognosticator of progression (p < 0.001), whereas WHO2004/2016 was not anymore (p = 0.067). C-indices for WHO1973, WHO2004, and the WHO systems combined for progression were 0.71, 0.67, and 0.73, respectively. Prognostic analyses for cystectomy and survival showed results similar to those for progression. CONCLUSIONS: In this large prognostic factor study, both classification systems were prognostic for progression but not for recurrence. For progression, the prognostic value of WHO1973 was higher than that of WHO 2004/2016. The four-tier combination (LG/G1, LG/G2, HG/G2, and HG/G3) of both WHO systems proved to be superior, as it divides G2 patients into two subgroups (LG and HG) with different prognoses. Hence, the current EAU-NMIBC guideline recommendation to use both WHO classification systems remains correct. PATIENT SUMMARY: At present, two classification systems are used in parallel to grade non-muscle-invasive bladder tumors. Our data on a large number of patients showed that the older classification system (WHO1973) performed better in terms of assessing progression than the more recent (WHO2004/2016) one. Nevertheless, we conclude that the current guideline recommendation for the use of both classification systems remains correct, since this has the advantage of dividing the large group of WHO1973 G2 patients into two subgroups (low and high grade) with different prognoses.
Keywords: Urology; Grade; European Association of Urology; Neoplasm Grading; prognóza; nádory močového měchýře; Non–muscle invasive; Cancer; World Health Organization; Urothelial; Aged; senioři; Bladder; 2004; lidé; Carcinoma; stupeň nádoru; Humans; 1973; Cystectomy; Prognosis; 2016; cystektomie; Urinary Bladder Neoplasms; Stage; urologie; Guideline; Progression